Note on m-polar fuzzy graph representation of concept lattice: How to really compute m-polar fuzzy concepts. (February 2019) - Konecny, Jan
Abstract: Singh (2018) claims to propose an extension of formal concept analysis for handling multi-polar information. For this setting he invents an algorithm. The aim of this note is two-fold: First, we show that Singh's algorithm is inefficient, since it is a direct generalization of one of the least efficient algorithms known in formal concept analysis, and strictly speaking, the algorithm is incorrect. Second, we are reminded that many algorithms already exist which can be used instead. This is because Singh's setting is already covered by a more general and well established framework of formal fuzzy concept analysis.